2016
DOI: 10.1177/1541931213601243
|View full text |Cite
|
Sign up to set email alerts
|

Effects of grip span in one-handed thumb interaction with a smartphone

Abstract: The purpose of this study was to investigate whether different grip spans affected the touch performance of one-handed thumb interaction with a smartphone. Tapping time, hit count, and thumb-tip displacement were measured while using three mock-ups of an iPhone 5S, 6, and 6 Plus, respectively. In the tapping task, four positions were tested: top-left, top-right, bottom-left, and bottom-right. The results showed that the hit count ( F2,14=8.596, p=.004) and thumb-tip displacement ( F2,14=11.348, p=.001) signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The device in this study was controlled to a 4" screen. However, with the large screen smartphones becoming increasingly popular for better experience in viewing content it is important to see how these (screen edge and screen corner) boundaries change with respect to the change in screen (along with change in grip) and hand sizes (Sung, Cho, & Freivalds, 2016). Therefore, testing with different device sizes and incorporating hand size in the stratification could have the potential to improve the study findings.…”
Section: Discussionmentioning
confidence: 99%
“…The device in this study was controlled to a 4" screen. However, with the large screen smartphones becoming increasingly popular for better experience in viewing content it is important to see how these (screen edge and screen corner) boundaries change with respect to the change in screen (along with change in grip) and hand sizes (Sung, Cho, & Freivalds, 2016). Therefore, testing with different device sizes and incorporating hand size in the stratification could have the potential to improve the study findings.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al [6] identified optimal reach zones for the back-side interaction on smartphones with different widths and lengths based on subjective discomfort and muscle activation data when various tasks were given. Sung et al [7] investigated the touch performance of one-handed thumb interactions with iPhone 5S, 6, and 6 Plus by measuring the tapping time, hit count, and thumb-tip and determined reachability issues for large smartphones. In addition, Chowdhury and Kanetkar [8] determined the preferred size of smartphones with hand anthropometry data and in terms of smartphone handiness.…”
Section: Introductionmentioning
confidence: 99%